INDONESIAN PISA RESULT: WHAT FACTORS AND WHAT SHOULD BE FIXED? - Ade Windiana Argina; Delsi Mitra; Nur Ijabah; Rozi Setiawan (Proceedings Education and Language International Conference, 2017)
One of the most prestigious programmes employed to measure educational achievement worldwide is Programme for International Student Assessment (PISA) offered by Organization for Economic Cooperation and Development (OECD). The core objective of PISA is to provide cross-nationally comparable evidence of student performance on the skills that are judged to be important for adult life (Breakspear, 2014). PISA result for Indonesia, as one of 72 countries joining PISA in 2015, pictured the stagnancy and failure of education performance system in this developing country. Attractively, it dragged the writers to conduct this study in purposing to identify the factors probably influencing the low position of Indonesia in PISA result during its participation. Based on the analysis, teachers’ quality, education system, education fund as well as educational decentralization are the most probable major factors influencing Indonesia PISA. To make this study more worthwhile, the writers also tried to seek and propose solutions bounding up with those analysed factors and education in the 21st century in purposing to be used as the reference for all elements of education in Indonesia and its stakeholders to improve the stagnancy and prevent the failure to engage with global demands in the 21st century. Keywords: PISA, Indonesia PISA result, Indonesia Educational System, Education Problems, the 21st Century Education.